Ascaris Lumbricoides Egg Detection from Digital Microscopic Fecal Sample Images - S.M., Sulong; Kamarul Hawari, Ghazali; Jasni, Mohamad Zain; Z., Mohamed (2012)
Diseases caused by intestinal parasite are alarming especially caused by AscarisLumbricoides. An efficient technique to detect existence of parasite automatically in fecal sample is vital. Therefore, this research is focus on detecting AscarisLumbricoides in fecal sample images by using digital image processing technique. There are four novel steps proposed in the detection process which are boundary detection, midpoint determination, radius distance calculation and parasite detection. The results generated are 100% precision and recall of 73%. This proves that this technique is a success.